Pembelajaran matematik: faktor kelemahan pelajar - Abu Hassan, Norihan; Khalid, Madihah (1992)
Getting a credit in Mathematics at the level of Sijil Pelajaran Malaysia is one of the entry requirement at Universiti Teknologi Malaysia. Although the requirement is such, lecturers in Mathematics find that most students are still weak in it. This paper attempt to identify the problems face by students when they learn Malhematics. Next is to recognize their study habits that is being practised by them; to know their motives on learning Mathematics and lastly to try to find a solution in order to increase their performance in Mathematics. Research findings are through the use of questionnaires and workshop (done in early 1991) by which students identify their own solution to the problems. Implications from this survey will hopefully help the various individuals in carrying out their job to increase the performance of students related to Mathematics.